An analysis on the electrophoretic mobility of cellulose nanocrystals as thin cylinders: relaxation and end effect. Issue 58 (22nd October 2019) - Lin, Kuan-Hsuan; Hu, Donghao; Sugimoto, Takuya; Chang, Feng-Cheng; Kobayashi, Motoyoshi; Enomae, Toshiharu
Abstract : Cellulose nanocrystals (CNCs) are extracted from cellulosic fibers via sulfuric acid hydrolysis and found to exhibit unique properties due to their nanoscale, ordered structure, and surface morphology. Abstract : Cellulose nanocrystals (CNCs) are extracted from cellulosic fibers via sulfuric acid hydrolysis and found to exhibit unique properties due to their nanoscale, ordered structure, and surface morphology. The dispersion stability of a CNC suspension is a significant factor when CNCs are applied for reinforcement of a composite or ink jet printing. Since sulfuric acid hydrolysis introduces sulfate groups on CNC surfaces, we considered that charging conditions needed to be characterized, typically based on electrophoretic mobility. After the electrophoretic mobility was measured, several theoretical equations were applied to fit those values to assume the proper CNC particle shape. While Smoluchowski's equation is often used for this purpose, its applicability to CNCs should be reconsidered due to the thin, rod-like shape of CNCs with a finite length and high charge density. In this sense, we measured the surface charge and electrophoretic mobility of well-characterized CNCs. The obtained experimental data have been analyzed by using various electrokinetic equations. Our analytical results suggested that Smoluchowski's equation and the Ohshima–Henry equation overestimated the magnitude of the mobility of CNCs because it ignores the double layer relaxation and end effect. They also suggested that neither the Ohshima–Overbeek averaged equation nor the Ohshima–Overbeek perpendicular equation described the mobility of CNCs appropriately because those equations consider the double layer relaxation and end effect of a cylinder in a limited manner. Instead, the modified Ohshima–Overbeek equation was presented to be preferred for such a charged cylinder with a small aspect ratio.